2017
DOI: 10.1016/j.infbeh.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress in the mother-infant dyad: Maternal hair cortisol, infant salivary cortisol and interactional synchrony

Abstract: Stress physiology is shaped by early experience, with enduring effects on health. The relation of chronic maternal physiological stress, as indexed by hair cortisol, to infants' stress systems and to mother-infant interaction quality has not been established. We examined maternal hair and salivary cortisol, six-month-old infants' salivary cortisol, and mother-infant interaction in 121 mother-infant dyads. High maternal hair cortisol was related to higher infant average salivary cortisol concentration. Maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 69 publications
(76 reference statements)
5
54
0
1
Order By: Relevance
“…Elevated child HCC has been related to increased stressful life events (Vanaelst et al, ). Prior studies have also established that higher parent HCC, lower socioeconomic status (SES), and poor parenting quality are related to increased levels of cortisol in young children (Flom, St. John, Meyer, & Tarullo, ; Kao, Doan, St. John, Meyer, & Tarullo, ; Karlén, Frostell, Theodorsson, Faresjö, & Ludvigsson, ; Ouellette et al, ; Tarullo, St. John, & Meyer, ; Vaghri et al, ; Vliegenthart et al, ). More research in early childhood is needed to understand the mechanisms for how early accumulation of stress throughout life can lead to poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated child HCC has been related to increased stressful life events (Vanaelst et al, ). Prior studies have also established that higher parent HCC, lower socioeconomic status (SES), and poor parenting quality are related to increased levels of cortisol in young children (Flom, St. John, Meyer, & Tarullo, ; Kao, Doan, St. John, Meyer, & Tarullo, ; Karlén, Frostell, Theodorsson, Faresjö, & Ludvigsson, ; Ouellette et al, ; Tarullo, St. John, & Meyer, ; Vaghri et al, ; Vliegenthart et al, ). More research in early childhood is needed to understand the mechanisms for how early accumulation of stress throughout life can lead to poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, several previous studies with mothers have shown that higher socioeconomic risk is associated with higher levels of cortisol (Bosquet Enlow et al, 2018;Clearfield, Carter-Rodriguez, Merali, & Shober, 2014;Tarullo, St. John, & Meyer, 2017;Thayer & Kuzawa, 2014;Ursache, Merz, Melvin, Meyer, & Noble, 2017). …”
Section: Stress and Parenting In The Context Of Socioeconomic Riskmentioning
confidence: 98%
“…Although cortisol has been studied significantly less than oxytocin in relation to maternal behaviour, the available studies report significant associations between high levels of maternal cortisol and compromised mother‐infant interactions. High postpartum maternal cortisol levels measured at rest have been associated with disrupted maternal behaviours, including decreases in infant‐directed maternal gaze, positive affect and vocalisation, and affectionate touch, as well as synchrony and positive engagement with infants . Increased maternal resting cortisol has also been associated with insecure attachment relationship between mother and infant, as well as decreased maternal sensitivity to infant cues .…”
Section: Maternal Hormones In Postpartum Depressionmentioning
confidence: 99%
“…Considering the importance of the infant's developing stress regulation in maternal postpartum adjustment as well as infant socio‐emotional development, much of the literature focusing on the HPA functions in the postpartum period have focused on the association between the mother's and the infant's HPA functions. Extensive research in this area has consistently documented that high levels of maternal cortisol predict high levels of infant cortisol . Furthermore, elevated cortisol levels in the mother during pregnancy and the postpartum period have been shown to negatively influence the infant's development, temperament and stress regulation .…”
Section: Maternal Hormones In Postpartum Depressionmentioning
confidence: 99%